Long non-coding RNAs and messenger RNA isoforms associated with muscle fatty acid profile in Nellore animals - Salatta, Bruna Salatta (2023)
In recent decades, considerable attention has been paid to the increase in beneficial fatty acids (FA) present in foods of animal origin. Traits of economic importance in beef cattle, as well as the meat fatty acid profile, are polygenic in nature and are influenced by genetic and environmental factors. In this sense, the RNA sequencing (RNA-Seq) is a technique employed to examine the expression of functional candidate genes, allowing the identification of significant molecular mechanisms that lead to variations in pathways responsible for distinct tissue phenotypes. Therefore, the objective was to study the transcriptome of Nellore cattle muscle, aiming to identify differentially expressed long non-coding RNAs (lncRNAs) and mRNA isoforms associated with FAs, through RNA-Seq. For this purpose, 48 animals were sequenced and phenotyped to seven individual FAs: myristic, palmitic, stearic, oleic, linoleic, conjugated linoleic, alpha-linolenic; and seven FA groups: sum of saturated FAs, monounsaturated FAs, polyunsaturated FAs, ω3, ω6, PUFA/SFA ratio, and ω6/ω3 ratio. K-means analysis was employed to cluster 48 animals into three groups based on their FA patterns. Cluster C1 exhibited significantly higher proportions (p ≤ 0.05) of polyunsaturated fatty acids (PUFA), including ω3, ω6, linoleic, and α-linolenic acids compared with C2 and C3. The proportion of monounsaturated fatty acids (MUFA) conjugated linoleic acid, and oleic acid in C2 and C3 was significantly (p ≤ 0.05) higher compared to C1, while C3 showed significantly higher proportions (p ≤ 0.05) of saturated fatty acids (SFA), myristic, palmitic, and stearic acids in comparison to the other clusters. For transcriptome analysis, a pairwise comparison experiment between two groups (C1 vs. C2, C1 vs. C3, and C2 vs. C3) was conducted. The results are presented in Chapters 2 and 3. In Chapter 2, a total of 265 long non-coding RNA (lncRNA) transcripts were differentially expressed (p-value < 0.01), being that 75, 113, and 78 identified in the C1 vs. C2, C1 vs. C3, and C2 vs. C3 comparisons, respectively. These lncRNAs were associated with genes belonging to the interferon, interleukin, G protein-coupled receptor, calponin, and apoptotic Bcl-2 families. Functional enrichment analysis revealed that many Gene Ontology (GO) terms were associated with the immune system in genetic profiles with higher saturated fatty acid (SFA) content (e.g, SERPINE1). In Chapter 3, a total of 65, 26, and 30 mRNA isoforms were differentially expressed (p-value < 0.01) in the C1 vs. C2, C1 vs. C3, and C2 vs. C3 comparisons, respectively. Additionally, differentially expressed isoforms, such as C7-203, ADD1-204, OXT-201 and RBM3-202, were linked to genes affecting polyunsaturated fatty acid content in the C1 vs. C2 comparions, while other mRNA isoforms important for saturated fatty acid content, such as EGR1-201, FOSB_mRNA1, and SERPINE1_mRNA1, were identified in the C1 vs. C2 comparison. Moreover, functional enrichment analysis highlighted various terms associated with fatty acid metabolism, as well as terms related to oxidoreductase activity, lipid transport, and immune response. This thesis provided insights into potential lncRNA and mRNA isoform candidates associated with FA in beef cattle, contributing to a better theoretical understanding of biological processes associated with this feature. This information may contribute to future research focused into identification of genetic markers to be applied in genetic selection of animals with better FA profiles.